Let it glow : a winter's walk - Gildersleeve, Owen (London Wide Eyed Editions, 2017)
Celebrate the holiday season with this book featuring real lights that glow with every turn of the page. Set in a winter wonderland, follow one child on his journey home through a snowy landscape. Lights are revealed by diecuts throughout, becoming lit-up shop windows, carol singers' candles, stars in the sky and finally a star on the tree. Told in verse, this gift book will bring the magic of Christmas into everyone's home. Age 3+.
"With real twinkling lights" --cover.
Keywords: Winter -- Juvenile fiction; Toy and movable books; Toy and movable books; Christmas fiction